Construction of Cultural Meaning Through Folk Literature: A Case Study of the Folk Literature of Say Fong and Phuen Wieng in Transliteration of the Palm-leaf Manuscripts at Srichomchuen Temple, Khok Lao Tai Village, Bu Hom Sub-district, Chiang Khan District, Loei Province 1 - Nunpooban, Suratadchanukoon (Dhammathas Academic Journal, 2023)
This study aims to explore and classify literature found in palm-leaf manuscripts, select relevant local literature for transliteration into modern Thai language, and identify cultural meanings of the Isan people through the transliterated texts. It is a qualitative research study, presenting data in a descriptive analysis format. The Diffusionism Theory was employed to uncover cultural meanings embedded in the stories. Findings: 1. A total of 110 literary works were discovered, comprising 477 sets of palm-leaf manuscripts. The manuscripts utilized Thamma-Isaan script, Pali script, Thai Noi script, and current Thai script. 2. Two stories, namely Sai Phong and Phueng Wiang, were transliterated. These literary works were recorded as having been written in the year 1243 as an offering to Wat Si Chom Chuen. This serves as evidence of the community’s identity and the longstanding relationship between the temple and the community. 3. Through the transliteration of the stories Sai Phong and Phueng Wiang, three cultural meanings were identified: (1) Cultural meanings expressing identity and ethnicity, (2) Spatial cultural meanings, and (3) Cultural meanings associated with Buddhism and ghosts. The data obtained from this study shed light on the people’s way of life, economic conditions, and societal concepts during that period. These valuable ancient documents deserve further study and preservation.